Analysis of Legal Protection of Buyers Against Breach of Performance in The Deed of Sale of Land Pledge at The People's Credit Bank - Meirizka, Feronika Ardella; Adillah, Siti Ummu (TABELLIUS: Journal of Law, 2025)
Abstract. A deed of sale and purchase can be considered the initial step towards the execution of a land rights sale and purchase agreement. Based on Article 1457 of the Civil Code, the creation of a deed of land sale and purchase does not require full payment as long as both parties agree. However, this often leads to legal issues later, including in cases where the seller is in default. The problem that will be discussed in this thesis is how the legal protection for buyers in the event of default in the sale and purchase agreement of land pledged at PT. Bank Perkreditan Rakyat Arthanugraha Makmursejahtera. What are the legal consequences of default in the sale and purchase agreement of land pledged at PT. Bank Perkreditan Rakyat Arthanugraha Makmursejahtera. What is the basis of the legal considerations of the Panel of Judges in the case of default on the Sale and Purchase Agreement made by the Notary for the land pledged at PT. Bank Perkreditan Rakyat Arthanugraha Makmursejahtera. This research is descriptive analysis and the research material is obtained using a normative juridical approach. The data collection technique used is a literature study. The collected data is then analyzed using a qualitative method supported by deductive logical thinking. Based on the research that has been conducted, it can be concluded that, the choice of resolution in the problems and solutions to joint property disputesThis sale and purchase agreement carried out by Mr. Abdul Khoir as the Buyer/Plaintiff against Mr. Masno bin Pardi as the Seller/Defendant is valid according to the applicable laws and regulations, because it fulfills the requirements for a valid agreement according to Article 1320 of the Civil Code.. The existence of the Deed of Sale and Purchase Agreement Number: 20 dated April 28, 2023 made before a Notary is legally valid. If any party has committed a breach of contract against the authentic deed, it must first be declared void by the Court, thus causing an error and leading to the cancellation of the deed. The Panel of Judges in providing legal considerations on case Number: 49/Pdt.G/2023/PN.Pwd was not careful and wrong and did not reflect a sense of justice for the community in seeking justice, especially for the Buyer/Plaintiff who clearly the Seller/Defendant had committed a breach of contract againstDeed of Sale and Purchase Agreement Number 20 dated April 28, 2023 made before a Notary. Keywords: Default; Land Sale and Purchase Deed; Legal Protection for Buyers.